2018
DOI: 10.7717/peerj.5335
|View full text |Cite
|
Sign up to set email alerts
|

Habitat and landscape factors influence pollinators in a tropical megacity, Bangkok, Thailand

Abstract: BackgroundPollinators are well known for the ecosystem services they provide, and while urban areas are generally perceived as low-quality habitat for most wildlife, these cities often support a surprising degree of pollinator diversity. The current rapid growth of urban areas and concern over global pollinator declines have spurred numerous studies examining pollinator communities in temperate cities, but knowledge about tropical urban pollinators remains scarce.MethodsThis study investigated the effects of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 54 publications
7
47
0
Order By: Relevance
“…For instance, in the shrinking city of Poznań, Poland, greater bee richness occurred with increased proximity to a large patch of greenspace with direct connection to suburban land cover (Banaszak‐Cibicka et al., 2016). Likewise, larger patch sizes were associated with increased bee richness and abundances in the growing city of Bangkok, Thailand (Stewart et al., 2018). In part, patch sizes are likely influential because they affect nesting site availability (Stewart et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the shrinking city of Poznań, Poland, greater bee richness occurred with increased proximity to a large patch of greenspace with direct connection to suburban land cover (Banaszak‐Cibicka et al., 2016). Likewise, larger patch sizes were associated with increased bee richness and abundances in the growing city of Bangkok, Thailand (Stewart et al., 2018). In part, patch sizes are likely influential because they affect nesting site availability (Stewart et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, larger patch sizes were associated with increased bee richness and abundances in the growing city of Bangkok, Thailand (Stewart et al., 2018). In part, patch sizes are likely influential because they affect nesting site availability (Stewart et al., 2018). Indeed, simultaneous work in Cleveland documented that native bees and wasps exhibit increased reproduction when a larger patch of greenspace was available within the urban landscape (KJ Turo, unpublished data), suggesting that habitat area may be a limiting factor for some urban bees.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation obviously largely depends on increasing the species of plants attractive to bees and lepidopterans rather than just generally increasing plant richness [ 83 ]. Floral abundance and frequency, however, may be more impactful than promoting richness itself [ 84 , 85 ]. Other factors including increased floral area (area occupied by blooming plants) have also been shown to influence butterfly and bee abundance [ 45 , 86 ].…”
Section: Local Featuresmentioning
confidence: 99%
“…Hongjamrassilp et al (2014) analyzed the pollen composition on the body of X. nasalis in Ratcha Buri province, Thailand, and found that the pollens were mostly native to the region of Southeast Asia, suggesting that X. nasalis is highly valuable for crop pollination [ 3 ]. Furthermore, stingless bees, Apis honey bees and Xylocopa carpenter bees are major pollinators in highly populated, tropical cities such as Bangkok [ 4 ].…”
Section: Introductionmentioning
confidence: 99%